Analysis of the Needs for Teaching Materials Text Report of Microblog Assisted Observations for Senior High School Students - Dewi jayana; Khaerudin Kurniawan; Yeti Mulyati (AL-ISHLAH: Jurnal Pendidikan, 2024)
The study investigates the adequacy and development methods of teaching materials, specifically textbooks, which are essential references for students. Despite their importance, current textbooks exhibit shortcomings in content sufficiency and development techniques. Given the technological inclinations of contemporary students, integrating technology into learning can enhance engagement and enjoyment. This research aims to analyze the necessity of microblog-based teaching materials for observation report texts to boost student enthusiasm and active participation in learning. Employing qualitative research methods, the study involved 96 students from three high schools in Takengon. Data were collected via Google Forms and analyzed descriptively. Findings indicate a significant demand for microblog teaching materials, with 80% of students responding affirmatively to the need for such resources. The study's implications include providing captivating teaching materials to enhance classroom learning and motivating teachers to create more engaging educational resources, thereby fostering greater student enthusiasm and participation.